2001
DOI: 10.1590/s0066-782x2001000200003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory evaluation of hyperlipemic and hypothyroid patients

Abstract: Objective -To determine the frequency of hypothyroidism in a sample of hyperlipemic patients and evaluate clinical and laboratory factors indicative of thyropathy among them. Methods -Fifty-one hyperlipemic patients, grouped according to an earlier or recent diagnosis of their thyroid function into euthyroid and hypothyroid, were evaluated with clinical and laboratory examinations of blood levels of free T 4 and TSH (by radioimmunoassay Clinical and Laboratory Evaluation of Hyperlipemic and Hypothyroid Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
(44 reference statements)
0
9
2
Order By: Relevance
“…Vierhapper et al [23] showed increased LDL-C levels in overt hypothyroidism, although not significant. Since thyroid hormones activate the gene expression of the LDL-C receptor in the liver, variability in the association between lipid profile and hypothyroidism is probably related to the gene expression variation [1,8,13]. The results of our study, in contrast to the study of Decastro et al [13], showed that mean HDL-C did not differ in these 3 groups.…”
Section: Endocrine Carecontrasting
confidence: 89%
See 1 more Smart Citation
“…Vierhapper et al [23] showed increased LDL-C levels in overt hypothyroidism, although not significant. Since thyroid hormones activate the gene expression of the LDL-C receptor in the liver, variability in the association between lipid profile and hypothyroidism is probably related to the gene expression variation [1,8,13]. The results of our study, in contrast to the study of Decastro et al [13], showed that mean HDL-C did not differ in these 3 groups.…”
Section: Endocrine Carecontrasting
confidence: 89%
“…Since thyroid hormones activate the gene expression of the LDL-C receptor in the liver, variability in the association between lipid profile and hypothyroidism is probably related to the gene expression variation [1,8,13]. The results of our study, in contrast to the study of Decastro et al [13], showed that mean HDL-C did not differ in these 3 groups. Effects of overt hypothyroidism on HDL-C and TG levels have been variable [1,14,24]; after adjusting for sex and age, no significant association was found between high levels of TC, TG, LDL-C, or low HDL levels and overt or subclinical hypothyroidism.…”
Section: Endocrine Carecontrasting
confidence: 89%
“…Serum concentrations of high density lipoprotein cholesterol was reported to be higher among newly diagnosed hypothyroid patients (subclinical or clinical) whereas serum concentrations of HDL cholesterol were significantly lower among euthyroid and previously reported hypothyroid cases who were on thyroxine replacement therapy 8 . Studies done by Michalopoulou 21 , Diekman 22 , Tsmihodimos 23 and Olukoga 24 showed average serum concentration of HDL higher in subclinical or clinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 76%
“…Serum concentration of high density lipoprotein cholesterol was reported to be higher among newly diagnosed hypothyroid patients with the value more than 40 mg/dL in subclinical or clinical hypothyroidism whereas serum concentrations of HDL cholesterol were significantly lower among euthyroid and previously reported hypothyroid cases who were on thyroid replacement therapy 8 . Hypothyroid patients usually exhibit elevated levels of high density lipoprotein cholesterol (HDL-C) mainly due to increased concentration of HDL2 particles 9 .…”
Section: Introductionmentioning
confidence: 79%
“…Similarly, Milionis et al [17] have found no alteration on plasma paraoxonase-1 activity in subclinical hypothyroid patients before and after levothyroxine therapy. It has been shown in several studies that serum concentration of HDL could be increased in subclinical hypothyroidism [18,19] . The underlying mechanism of the elevated HDL concentration in hypothyroidism is not clear.…”
Section: Discussionmentioning
confidence: 99%